The adsorption potential of andisol/zeolite/fly ash as adsorbents on chromium hexavalent removal. Issue 1 (1st March 2022) - Mustofa, R E; Inayati; Pranoto
Abstract: The study of Andisol/Zeolite/Fly ash (AZF) as adsorbents has been investigated. This research was aimed to study the characteristics of AZF as an adsorbent for Chromium metal ion removal. Andisol soil and zeolite were activated using NaOH solutions. All materials were characterized by Fourier Transform Infrared (FTIR), Surface Area Analyzer (SAA), and Ultraviolet-Visible Spectrometry (UV-Vis). Based on the results, the optimum composition of AZF was obtained at the ratio of andisol/zeolite/fly ash of 2.4/2.4/0.2 (w/w%), with a decrease on Chromium(VI) concentration above 92%. The optimum condition occurred at a pH of 3 and 150 minutes of contact time. The isotherm study showed that Freundlich isotherm was more dominant rather than Langmuir isotherm.